Developing Guidelines for Mentoring-Supervision in the School under the Office of Udonthani Primary Educational Service Area 4 - ๋Jaihan Orawan; Amornpan, Suracha (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2021)
The objectives of this research article were 1) to study the current state and the desirable state of mentoring-supervision of schools under Udonthani primary educational service area office 4, 2) to developing the mentoring-supervision guidelines of schools under Udonthani primary educational service area office 4. The sample group consisted of 375 administrators and teachers. Key informants were administrators and teachers from 3 pilot schools and 5 luminaries. Research instruments were questionnaire, interview and guideline assessment form. Statistics for analyses data were mean, percentage, standard deviation and PNImodified. The research result were found that: 1. The current state of mentoring-supervision of schools under Udonthani primary educational service area office 4 overall were at moderate level and the desirable state overall were at high level. 2. The guidelines of mentoring-supervision of schools under Udonthani primary educational service area office 4 consisted of 3 aspects 24 guidelines 1) supervision prepare and plan meeting 2) mentoring-supervision implementation 3) supervision assessment and recommendation. Guidelines assessment by 5 luminaries were found the guidelines suitability overall were at high levels and the guidelines possibility overall were at highest levels.